2019
DOI: 10.1111/1440-1703.12061
|View full text |Cite
|
Sign up to set email alerts
|

Drift and emergence patterns of nonbiting midges (Chironomidae, Diptera, Insecta) in a subtropical river

Abstract: The passive dispersal of macroinvertebrates suspended in the water column is known as drift. In tropical and subtropical rivers, which show a distinct hydrological cycle with defined flood and dry periods, chironomids may use flood periods for effective downstream dispersal, particularly if drift coincides with emergence, due to lower fish predator efficiency because of increased turbidity and turbulence. If this is true, chironomids should display a seasonal drift and emergence pattern. The abundances in drif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
(30 reference statements)
0
1
0
Order By: Relevance
“…For example, Brittain & Eikeland (1988) found that Ephemeroptera, Simuliidae, Plecoptera and Trichoptera were the most abundant aquatic insects in a diel drift evaluation. Likewise, Schulz, Rosa, & Klein-Stolz (2019) found that Chrironomidae comprised 70% of the total macroinvertebrates drifting in a Neotropical River in Southern Brazil.…”
Section: Discussionmentioning
confidence: 96%
“…For example, Brittain & Eikeland (1988) found that Ephemeroptera, Simuliidae, Plecoptera and Trichoptera were the most abundant aquatic insects in a diel drift evaluation. Likewise, Schulz, Rosa, & Klein-Stolz (2019) found that Chrironomidae comprised 70% of the total macroinvertebrates drifting in a Neotropical River in Southern Brazil.…”
Section: Discussionmentioning
confidence: 96%